Ferroelectric and electromechanical performance of diverse engineered states of Mn-doped 0.75Pb(Mg1/3Nb2/3)O3-0.25PbTiO3 ceramics. Issue 13 (1st July 2021) - Cheng, Mingqiang; Zhao, Erding; Jiang, Fangjian; Jiang, Xiaodong; Fang, Ze; Li, Feng; Ye, Wanneng; Qin, Yalin; Zhang, Yongcheng
Abstract: The materials processing history has a great influence on their properties and finally determines their application effect. In this paper, the ferroelectric, polarization-switching current, and strain properties of Mn-doped 0.75Pb(Mg1/3 Nb2/3 )O3 -0.25PbTiO3 ceramics were studied in fresh state, aged state, and poled state, respectively. Compared with the symmetric polarization-electric-field ( P - E ) hysteresis loops, current-density-electric-field ( J - E ) curves, and bipolar electric-field-induced strain ( S - E ) curves in fresh state samples, asymmetric P-E loops, J - E curves, and bipolar S - E curves were obtained in poled state samples. Well-aged-state samples exhibit double hysteresis P - E loop, four peaks J-E curves, and symmetric S-E curves without negative strain. The symmetry-conforming short-range order (SC-SRO) principle of point defects and internal electric field E i is employed to clarify the different phenomenon of three states. Results indicated that randomly oriented defect polarization P D in aged samples can reverse the spontaneous polarization P S back and result in the double hysteresis P - E loop and four peaks J-E curves. The oriented P D and resulting E i in poled-state samples will lead to the asymmetric loops and strain memory effect.